SIMULASI PH AIR UNTUK AIR BOILER DAN AIR CHILLER PADA MESIN PRODUKSI REFRIGERATOR DENGAN MENGGUNAKAN LOGIKA FUZZY - Irawan, Andhika; Heranurweni, Sri; Nurhayati, Titik (Universitas Semarang, 2019)
The need for water is very important for the production process, the water quality must also be considered the pH value so that the water is suitable for use in boilers or chillers. Seeing from these needs a simulation was made on matlab R2017a using a fuzzy toolbox that can find out the water quality with fuzzy mamdani method. This fuzzy logic simulation can determine the standard value of boiler water pH (10.5-11.5) and the standard pH value of chiller water (6-8) in the production machine. The methods in fuzzy logic used are mamdani and centroid methods as deffuzification with R2017a matlab simulation tool. The fuzzy inference system used is the mamdani method. This study made a simulation of mamdani method that can determine the quality of the PH water produced by using fuzzy logic. Chiller water pH can be used if iron ion values (0-2 ppm), silica ions (50-150 ppm), Total Dissolved Solid (TDS) (500-1000 ppm), total Hardness (100-200 ppm), M-alkalinity (500-750 ppm) from the standard value, the pH of the chiller water can be proven to reach a water pH value of 6-8. Boiler water pH can be used if iron ion values (0-2 ppm), silica ions (100-150 ppm), Total Dissolved Solid (TDS) (2000-3500 ppm), total Hardness (0-3 ppm), M-alkalinity (700-800 ppm) from the standard value, the pH of boiler water can be proven to reach a water pH value of 10.5-11.5.Keywords: fuzzy logic, Mamdani method, pH of boiler water